2019
DOI: 10.1002/hed.25814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking cessation on clinical outcomes in patients with head and neck squamous cell carcinoma receiving curative chemoradiotherapy: A prospective study

Abstract: Background We hypothesized that patients with head and neck squamous cell carcinoma (HNSCC) with smoking cessation during curative chemoradiotherapy (CRT) had fewer complications and lower tumor progression risks. Methods Sixty‐three patients with nonmetastatic HNSCC who were smokers at diagnosis (carbon monoxide [CO] breath concentrations ≥3 ppm) and underwent curative CRT were prospectively enrolled. Successful smoking cessation throughout CRT was confirmed by CO breath concentrations <3 ppm at CRT completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…For example, several retrospective and prospective HNC cohort studies with variable or unspecified times of outcome assessment have reported high abstinence rates ranging from 46% to 65%. [6][7][8][9]30,31 High cessation rates were also reported by the Collaborative Breast Cancer and Women's Longevity Study: among 20 961 patients with breast cancer followed for a median of 12 years, only 10% of women who smoked within 1 year of diagnosis continued smoking after diagnosis (n = 434/4059). On the other hand, a large observational study of currently smoking thoracic center patients (n = 342) at the Roswell Park Cancer Institute described much lower cessation rates: 20% of patients reported smoking cessation at an average follow-up of 49 days.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, several retrospective and prospective HNC cohort studies with variable or unspecified times of outcome assessment have reported high abstinence rates ranging from 46% to 65%. [6][7][8][9]30,31 High cessation rates were also reported by the Collaborative Breast Cancer and Women's Longevity Study: among 20 961 patients with breast cancer followed for a median of 12 years, only 10% of women who smoked within 1 year of diagnosis continued smoking after diagnosis (n = 434/4059). On the other hand, a large observational study of currently smoking thoracic center patients (n = 342) at the Roswell Park Cancer Institute described much lower cessation rates: 20% of patients reported smoking cessation at an average follow-up of 49 days.…”
Section: Discussionmentioning
confidence: 85%
“…A proliferation of primarily observational studies have reported nonstandardized, wide‐ranging abstinence outcomes for all cancer types. For example, several retrospective and prospective HNC cohort studies with variable or unspecified times of outcome assessment have reported high abstinence rates ranging from 46% to 65% 6‐9,30,31 . High cessation rates were also reported by the Collaborative Breast Cancer and Women's Longevity Study: among 20 961 patients with breast cancer followed for a median of 12 years, only 10% of women who smoked within 1 year of diagnosis continued smoking after diagnosis (n = 434/4059).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Chen et al's prospective study demonstrated smoking cessation during curative chemoradiotherapy for 63 patients with head and neck squamous cell carcinoma. 12 Forty-one patients (65%) successfully discontinued smoking throughout chemoradiotherapy (CRT). During a median 33-month follow-up period, the patients with successful smoking cessation during CRT presented significantly fewer acute toxicities (p = .01) and reduced tumor progression risks (hazard ratio: 0.4, p = .05).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, heavy smokers (>1 pack/day) had significantly poorer outcomes of 5‐year locoregional control (44 vs. 65%, p = .001), disease‐specific (56 vs. 77%, p = .003), and overall survival (39 vs. 66%, p = .0004) compared to non‐smokers. Chen et al's prospective study demonstrated smoking cessation during curative chemoradiotherapy for 63 patients with head and neck squamous cell carcinoma 12 . Forty‐one patients (65%) successfully discontinued smoking throughout chemoradiotherapy (CRT).…”
Section: Discussionmentioning
confidence: 99%